2011
DOI: 10.1016/j.iccn.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Surviving a critical illness through mutually being there with each other: A grounded theory study

Abstract: Objectives:The objectives of this study were to conduct a theoretical analysis of the critically ill patients' perceptions of the impact of informal support and care from their main family carer (MFC) during the time of their stay in the hospital (ICU) and thereafter (and vice versa). Research design and setting: The grounded theory method was used to investigate the target phenomenon in the ICU of a large general hospital, and three months later in the community after the patients were discharged. Qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 47 publications
(49 reference statements)
1
42
0
Order By: Relevance
“…In addition, gratitude emerged from five studies, where patients felt thankful for surviving critical illness, with deeper appreciation of the value of life [3639, 46]. Independence was identified in four studies, with patients commenting on the value of being able to do basic tasks without assistance [16, 18, 40, 41]. On the contrary, patients in four studies commented on having negative emotions related to satisfaction with life; themes generated from these studies included boredom [37], loneliness/isolation [38, 44], and feeling that they wish they had not lived [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, gratitude emerged from five studies, where patients felt thankful for surviving critical illness, with deeper appreciation of the value of life [3639, 46]. Independence was identified in four studies, with patients commenting on the value of being able to do basic tasks without assistance [16, 18, 40, 41]. On the contrary, patients in four studies commented on having negative emotions related to satisfaction with life; themes generated from these studies included boredom [37], loneliness/isolation [38, 44], and feeling that they wish they had not lived [35].…”
Section: Resultsmentioning
confidence: 99%
“…This was highlighted by patients reporting about the importance of regaining mobility, even if only partially [16, 18, 37, 38, 40]. Also important was regaining the capacity to perform activities of daily living, identified in five studies, which appears to be important for both patients [16, 48, 50] and caregivers [18, 41]. Fatigue and subjective feeling of weakness were identified in four studies [16, 18, 33, 50].…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining a healthy level of independence may be important to improve long-term well-being of both the family caregiver and the ICU survivor. A qualitative study exploring the dynamics of the caregiver-survivor relationship up to 3 months post-ICU discharge [12] similarly observed the importance of the shift toward patient independence for optimal recovery. In the present study, we observed that disruptions in this shift toward patient independence were associated with strained survivorcaregiver relationships up to 2 years post-ICU discharge.…”
Section: Discussionmentioning
confidence: 98%
“…Despite this, much of the information desired by family members when making decisions is not provided, in particular, information about expected care needs and prognosis [10]. Some studies have begun to highlight the complex interdependency of ICU survivors and their family caregivers [11,12]. Caregivers discussed a lack of support from health care professionals post-ICU [12] and the importance of coping strategies to deal with the new disability [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation